Postnatal Preventive Effect of Magnesium Sulfate on Intraventricular Hemorrhage of Preterm Infants - Ashraf Mohammadzadeh; Ahmad Shah Farhat; Reza Saeidi; Marziyeh Roshandel; Azin Vaezi (Mashhad University of Medical Sciences, 2020)
Background: Germinal matrix hemorrhage and intraventricular hemorrhage (GMH-IVH) are among the causes of morbidity and mortality in very low birth weight (VLBW) neonates. The aim of this study was to determine the postnatal prophylactic effect of magnesium sulfate on GMH-IVH. Methods: In this double-blind clinical trial, 140 VLBW newborns were selected. The babies with birth weight ≤ 1500 g and gestational age ≤ 32 weeks were included. The babies with major malformation, infection, hemostatic disorders, severe cardio-respiratory failure, as well as asphyxia and resuscitation in the delivery room were excluded. They were randomly divided into two groups using a coin. The case group received 50% magnesium sulfate 4 mg/kg/day as a single dose via intravenous injection over 15-20 min for 3 days. All babies had a head ultrasound (HUS) in 24 to 48 h after birth, and if it was normal they were included in the study. The HUS was repeated in 1, 2, and 3 weeks after birth by a radiologist who did not know about the intervention. The control group received placebo sterile water in a dose similar to magnesium sulfate. The magnesium level was measured on day 4 at the end of the treatment. Results: Although GMH-IVH was two times more in the control group, the difference was not statistically significant between the two groups (P>0.05). The difference in the grading of IVH was not also significant between the two groups (P=0.25). The level of magnesium sulfate was significantly higher in the case group (P=0.04). Conclusion: The results of this study showed that the postnatal administration of magnesium sulfate has no effect on the prevention of IVH.